Adubação nitrogenada e aplicação de etileno ao final do ciclo de produção em mudas de Eucalyptus grandis Hill e Luehea divaricata - Schulz, Deisinara Giane (2015)
The formation of the changes is a phase of extreme importance for the success of any forest stand, for a change malformed, weakened, threaten the overall development, causing loss of production, and therefore any production process aimed at higher quality seedlings produced. Fertilization and acclimation to the end of the production cycle, are extremely important to promote morphological and physiological changes that enhance the growth and minimize stress damage after field planting. This study aimed to evaluate nitrogen fertilization during the production of whips-horse seedlings (Luehea divaricata Mart.) and eucalyptus (Eucalyptus grandis Hill ex Maiden) and quantify changes in morphogenesis after the application of ethylene in plants during hardening. The experiment was conducted in a greenhouse at the State University of Paraná West - UNIOESTE, campus Marechal Cândido Rondon-PR, latitude 24 ° 33 'S, longitude 54 ° 04' W. The work was carried out in a randomized block design in factorial with Additional Witness (3 x 4+1), being used three forms of fertilization (100 mg L-1 conventional N x 100 mg L-1 exponential N x N zero) applied for three months (nine applications) and five treatments with different application rates ethylene, with 6 replicates of five plants per plot. The measured variables were increase of height (IH) and stem diameter (DC), leaf area (LA), dry weight of shoots (MSA), dry weight of roots (MSR), Dickson quality index (IQD) and the activity of peroxidase and lignin content. The results were submitted to analysis of variance and Tukey test at 5% probability using the Genes program. The exponential and conventional fertilization sustain growth induction hypothesis L. divaricata seedlings and E. grandis for fertilization without nitrogen application in the growth phase, these same effects can be observed in the hardening phase with ethylene spray. The weekly sprays of ethylene induce changes in growth in the hardening phase in L. divaricata seedlings and E. grandis with two gas applications, mainly by reducing the aerial growth, reducing the leaf area and increasing stem size